B. MIGOTTI, Evidence for Christianity in Roman Southern Pannonia (Northern Croatia), A Catalogue of finds and sites, (BAR International Series 684), Oxford (Archaeopress, Publishers of British Archaeological Reports), 1997. 117p - Kuntić-Makvić, Bruna (Array, 1998)
-